After the Crisis : Assessing the Damage in Italy - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2010)
Italy's deep-rooted structural problems resulted in an unsatisfactory productivity performance and a dismal growth over the last 15 years. The global financial crisis has exacerbated these long-standing weaknesses, taking a heavy toll on Italy's economy. With output back to its end-2001 level, Italy's output losses associated with the crisis have been, thus far, about 132 billion of 2000 euro (around 10 percent of precrisis 1998 - 2004 real GDP). About three quarters of these losses are estimated to be due to a shortfall in potential output. Potential output is not expected to rebound to its precrisis trend over the medium term, even though growth is projected to do so within the next two years. In the short-run, the decline in output is mainly accounted for by a collapse in productivity; in the medium term, employment and capital are also likely to be affected, with implications for the longer-term growth and fiscal outlook.